High Sensitivity of T-Ray for Thrombus Sensing - Sun, Chi-Kuang; Chen, Hui-Yuan; Tseng, Tzu-Fang; You, Borwen; Wei, Ming-Liang; Lu, Ja-Yu; Chang, Ya-Lei; Tseng, Wan-Ling; Wang, Tzung-Dau (Scientific reports, 2018)
Atherosclerotic plaque rupture or erosion and subsequent development of platelet-containing thrombus formation is the fundamental cause of cardiovascular disease, which is the most common cause of death and disability worldwide. Here we show the high sensitivity of 200–270 GHz T-ray to distinguish thrombus formation at its early stage from uncoagulated blood. A clinical observational study was conducted to longitudinally monitor the T-ray absorption constant of ex-vivo human blood during the thrombus formation from 29 subjects. Compared with the control group (28 subjects) with uncoagulated blood samples, our analysis indicates the high sensitivity of 200–270 GHz T-Ray to detect thrombus with a low p-value < 10 −5 . Further analysis supports the significant role of platelet-activated thrombotic cascade, which modified the solvation dynamics of blood and occurred during the early coagulation stage, on the measured T-Ray absorption change. The ability to sense the thrombus formation at its early stage would hold promise for timely identification of patients at risk of various atherothrombotic disorders and save billions of lives.